(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
Aloe is a plant that is used against skin irritation, skin exposure to UV and gamma radiation, scalds, sunburn wounds, eczema, psoriasis, acne, dermatitis, ulcers, and to stimulate cell regeneration. This study aimed to determine the antibacterial activity of ethanolic and gel extracts of Aloe vera against certain clinical bacterial isolates. The extracts were screened for phytochemicals, and their antibacterial activities were determined using the well diffusion method at concentrations of 50, 100, 200, and 400 mg/mL. The result of phytochemical screening indicates the presence of alkaloids, flavonoids, tannins, anthraquinones, and steroids in both extracts. The result of the antibacterial assay revealed that both ethanolic and gel extracts of Aloe vera were active against E. coli at different concentrations, with zones of inhibition ranging from 25.5 mm to 20 mm. However, S. aureus shows resistance to the different concentrations of the extracts. Findings show that S. aureus was sensitive to ciprofloxacin, while resistant to Augmentin. Thus, the observed antibacterial resistance confirms S. aureus as a multi-drug-resistant strain, thereby justifying its resistance to the Aloe vera plant. This study suggests that the Aloe vera plant contains antibacterial properties.